PENGEMBANGAN E-MODUL BERBASIS ANDROID PADA MATA PELAJARAN INFORMATIKA DI SMK N 9 PADANG - Pedi Rianda; Edidas; Dedy Irfan; Rizky Ema Wulansari (Postgraduate, University of Mataram, 2025)
This research aims to develop an Android-based E-Module as a learning medium for Informatics subjects. The E-Module is designed to enhance students’ interest, motivation, and learning outcomes, enabling them to better understand the material comprehensively. The study adopts the IDI (Instructional Development Institute) method, which includes the stages of define, develop, and evaluate. Primary data collected from media experts, lecturers, and students were analyzed using descriptive analysis to assess the validity, practicality, and effectiveness of the media. The findings reveal that, The E-Module is highly valid in terms of material (0.94) and media aspects (0.94). Its practicality is rated as practical by teachers (88.33%) and very practical by students (93.55%). The E-Module effectively improves student learning outcomes, with an increase in the number of students meeting the KKM standard to 88.33%. In conclusion, the E-Module is valid, practical, and effective as a learning medium for enhancing students’ interest, motivation, understanding, and competence.